Succeed to culture a novel lineage symbiotic bacterium of Mollicutes which widely found in arthropods intestine uncovers the potential double-edged sword ecological function - Zhang, Lingyu; Chen, Qi; Zeng, Shenzheng; Deng, Zhixuan; Liu, Zhongcheng; Li, Xuanting; Hou, Qilu; Zhou, Renjun; Bao, Shicheng; Hou, Dongwei; Weng, Shaoping; He, Jianguo; et al. (Frontiers in Microbiology, 2024)
Symbiotic gut bacteria play crucial role in host health. Symbionts are widely distributed in arthropod intestines, but their ecological functions are poorly understood due to the inability to cultivate them. Members of Candidatus Bacilliplasma (CB) are widely distributed in crustacean intestine and maybe commensals with hosts, but the paucity of pure cultures has limited further insights into their physiologies and functions. Here, four strains of representative CB bacteria in shrimp intestine were successfully isolated and identified as members of a novel Order in the Phylum Mycoplasmatota. Through genome assembly, the circular genome maps of the four strains were obtained, and the number of coding genes ranged from 1,886 to 1,980. Genomic analysis suggested that the bacteria were missing genes for many critical pathways including the TCA cycle and biosynthesis pathways for amino acids and coenzyme factors. The analysis of 16S amplification data showed that Shewanella, Pseudomonas and CB were the dominant at the genera level in the intestine of Penaeus vannamei. Ecological functional experiments revealed that the strains were symbionts and colonized shrimp intestines. Our valued findings can greatly enhance our understanding and provides new insights into the potentially significant role of uncultured symbiotic bacteria in modulating host health.